Comparison of NITAG policies and working processes in selected developed countries. Issue 1 (1st January 2015) - Ricciardi, G.W.; Toumi, M.; Weil-Olivier, C.; Ruitenberg, E.J.; Dankó, D.; Duru, G.; Picazo, J.; Zöllner, Y.; Poland, G.; Drummond, M.
Highlights: NITAG recommendation is critical for vaccine market access. Comparison of NITAG policies was performed in 13 selected developed countries. Vaccine processes are heterogeneous, less structured, less transparent than HTA for other drugs. There is a need for improving the decision framework for NITAG recommendations. Abstract: Background: Vaccines are specific medicines characterized by two country-specific market access processes: (1) a recommendation by National Immunization Technical Advisory Group (NITAG), and (2) a funding policy decision. Objectives: The objective of this study was to compare and analyze NITAGs of 13 developed countries by describing vaccination committees' bodies and working processes. Methods: Information about NITAGs bodies and working processes was searched from official sources from June 2011 to November 2012. Retrieved information was completed from relevant articles identified through a systematic literature review and by information provided by direct contact with NITAGs or parent organizations. An expert panel was also conducted to discuss, validate, and provide additional input on obtained results. Results: While complete information, defined as 100%, was retrieved only for the UK, at least 80% of data was retrieved for 9 countries out of the 13 selected countries. Terms of references were identified in 7 countries, and the main mission for all NITAGs was to provide advice for National immunization programs. However, these terms of references did not fully encompass all the actual missions of the NITAGs. Decision analysis frameworks were identified for 10 out of the 13, and all NITAGs considered at least four criteria for decision-making: disease burden, efficacy/effectiveness, safety and cost-effectiveness. Advices were published by most NITAGs, but few NITAGs published meeting agendas and minutes. Only the United States had open meetings. Conclusions: This study supports previous findings about the disparities in NITAGs processes which could potentially explain the disparity in access to vaccinations and immunization programs across Europe. With NITAGs recommendations being used by policy decision makers for implementation and funding of vaccine programs, guidances should be well-informed and transparent to ensure National Immunization Programs' (NIP) credibility among the public and health care professionals.